Molecular interactions of the CTLA-4 cytoplasmic region with the phosphoinositide 3-kinase SH2 domains. (March 2021) - Iiyama, Momoka; Numoto, Nobutaka; Ogawa, Shuhei; Kuroda, Masataka; Morii, Hisayuki; Abe, Ryo; Ito, Nobutoshi; Oda, Masayuki
Highlights: The crystal structure of CTLA-4 and PI3K cSH2 complex was determined. The structure of CTLA-4 and PI3K nSH2 complex was modeled. The CTLA-4 binding affinity of cSH2 was higher than that of nSH2. The binding affinity of CTLA-4 to PI3K SH2s was lower than that of CD28. Abstract: During T-cell regulation, T-cell receptors and CD28 lead to signaling activation, while T-lymphocyte antigen 4 (CTLA-4) is known to lead to downregulation, similar to programmed cell death-1 (PD-1). In the cytoplasmic tails of CD28 and CTLA-4, phosphoinositide 3-kinase (PI3K) binds to the consensus sequence including phosphotyrosine via SH2 domains, N- and C-terminal SH2 domains (nSH2 and cSH2), of its regulatory subunit, p85. In this study, we determined the crystal structure of a CTLA-4-derived phosphopeptide in complex with a Cys-substituted mutant of cSH2, C656S/C659V/C670L, at a 1.1 Å resolution. Phosphotyrosine of the bound peptide is tightly accommodated by the residues Arg631, Arg649, Ser651, and Ser652, similar to the cSH2 wild-type recognition mode of CD28, as reported previously. Upon the Cys mutation, the cSH2 thermal stability increased while the CTLA-4 binding affinity slightly changed. The binding experiments also showed that the binding affinity of CTLA-4 by cSH2 was approximately two orders of magnitude lower than that of CD28. Similar to CD28 binding, the CTLA-4 binding affinity of nSH2 was lower than that of cSH2. The complex structure of nSH2 and CTLA-4 was modeled, and compared with the crystal structure of cSH2 mutant and CTLA-4. The difference in the binding affinity between CD28 and CTLA-4, along with the difference between nSH2 and cSH2, could be explained by the 3D structures, which would be closely correlated with the respective T-cell signaling.